O-Methyl Phytocannabinoids: Semi-synthesis, Analysis in Cannabis Flowerheads, and Biological Activity - Caprioglio, Diego; Allegrone, Gianna; Pollastro, Federica; Valera, Stefano; Lopatriello, Annalisa; Collado, Juan A.; Munoz, Eduardo; Appendino, Giovanni; Taglialatela-Scafati, Orazio (Planta Medica, 2019)
A general protocol for the selective mono-O-methylation of resorcinyl phytocannabinoids was developed. The availability of semisynthetic monomethyl analogues of cannabigerol, cannabidiol, and cannabidivarin (1a–3a, respectively) made it possible to quantify these minor phytocannabinoids in about 40 different chemotypes of fiber hemp. No chemotype significantly accumulated mono-O-methyl cannabidiol (2b) or its lower homologue (3b), while at least three chemotypes containing consistent amounts (≥ 400 mg/kg) of O-methylcannabigerol (1b) were identified. O-Methylation of alkyl phytocannabinoids (1b–3b) does not significantly change the activity on peroxisome proliferator-activated receptors in contrast to what was reported for phenethyl analogues.
Keywords: Cannabis sativa; Cannabaceae; meroterpenoids; phytocannabinoids; O-methylation; PPAR